Quality Control on Minimizing Defect Product on 20 OE Yarn - Arinda Soraya Putri; Fitdhan Primananda (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2021)
Industrial businesses in Indonesia realize that consumer desires have changed over time. Consumers desire that becomes the main priority is quality. PT. Bitrate Industries, as a company that produces yarn in Semarang, always strives to improve product quality to the desires of consumers. The company faces quality control problems: the production process of 20 OE yarn, producing the highest defective products. The Six Sigma approach analyzes the causes of defects, identifies sources of variation, proposes improvements with 5W + 1H, and implements a quality control plan. Most defects occur in the production process in the autocross engine, which is caused by engine wear. Implementation of the kaizen approach can be given proposals in the form of improvements in maintenance, according to the existing scheduling and periodic replacement of parts. This study concludes that the proportion of defects is still in the controlled stage, but the quality control of the product is still needed. A quality improvement project with a Six Sigma approach can benefit any company that needs to find the most efficient way to improve product quality.